The pleiotropic response regulator DegU functions as a priming protein in competence development in Bacillus subtilis - Hamoen, Leendert W. (The National Academy of Sciences, 2000)
The response regulator DegU is involved in various late-growth developmental processes in Bacillus subtilis, including the production of degradative enzymes and the development of genetic competence. DegU is essential for the expression of the competence transcription factor, encoded by comK. ComK is required for the transcription of genes encoding the DNA uptake and integration machinery, as well as for the transcription of its own gene. We have purified DegU to study its role in the expression of comK, and we demonstrate here that DegU binds specifically to the comK promoter. The binding of the response regulator DegU to a promoter target had not been reported previously. DNase I protection analyses show that the DegU binding site overlaps with the ComK binding site, and gel retardation experiments indicate that DegU strongly stimulates the binding of ComK to the comK promoter. We propose that DegU functions at the initiation of competence development, when ComK concentrations are insufficient to support comK transcription, by facilitating ComK binding to the comK promoter. DegU therefore acts as a priming protein that primes the autostimulatory transcription of comK. Such priming activity adds a function to the class of response regulator proteins.